2016
DOI: 10.1007/s00213-016-4480-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute oxytocin improves memory and gaze following in male but not female nursery-reared infant macaques

Abstract: Rationale Exogenous oxytocin administration is widely reported to improve social cognition in human and nonhuman primate adults. Risk factors of impaired social cognition, however, emerge in infancy. Early interventions—when plasticity is greatest—are critical to reverse negative outcomes. Objective We tested the hypothesis that oxytocin may exert similar positive effects on infant social cognition, as in adults. To test this idea, we assessed the effectiveness of acute, aerosolized oxytocin on two foundatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…This finding suggests that: (i) OT increases interactive social behaviors; (ii) gaze-following, an interactive behavior elicited by videos, is unrelated to the time spent looking at the eyes; and (iii) looking at the eyes of static images may not be a good measure for the effect of OT on natural, interactive social behaviors. A similar finding was reported in infant rhesus monkeys but the increase in the frequency of gaze-following behaviors was observed only in males and not females (Simpson, Paukner, et al, 2017). It is possible that many of these socio-behavioral effects of OT are sex-specific.…”
Section: Studies Of Oxytocin In Non-human Primatessupporting
confidence: 86%
“…This finding suggests that: (i) OT increases interactive social behaviors; (ii) gaze-following, an interactive behavior elicited by videos, is unrelated to the time spent looking at the eyes; and (iii) looking at the eyes of static images may not be a good measure for the effect of OT on natural, interactive social behaviors. A similar finding was reported in infant rhesus monkeys but the increase in the frequency of gaze-following behaviors was observed only in males and not females (Simpson, Paukner, et al, 2017). It is possible that many of these socio-behavioral effects of OT are sex-specific.…”
Section: Studies Of Oxytocin In Non-human Primatessupporting
confidence: 86%
“…In total, the search process yielded 80 unique studies. Based on the titles and abstracts, 68 studies were rejected . Based on full text review of the remaining 12 studies, five were rejected for being short‐term studies (less than a month), while one was rejected for not being a randomized controlled trial .…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that our study revealed a more pronounced effect of OXT on NAcc activation to partner touch in female participants. Gender‐specific OXT effects have been found in various animal [Kelly and Goodson, ; Li et al, ; Simpson et al, ; Steinman et al, ; Young and Wang, ] and human [Ditzen et al, ; Feng et al, ; Hoge et al, ; Lischke et al, ; Scheele et al, ; Yao et al, ] studies. Specifically, intranasal OXT enhanced striatal responses to reciprocated cooperation in a Prisoner's Dilemma Game in men, but not in women [Rilling et al, ].…”
Section: Discussionmentioning
confidence: 99%